2020
DOI: 10.1111/fare.12529
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perspectives on the Impact of Their Incarceration on Children and Families

Abstract: ObjectiveTo qualitatively explore the impact of parental incarceration on children and families from the perspective of the incarcerated parent in a county jail.BackgroundAn estimated 5 million U.S. children experience parental incarceration. A limited number of studies have examined the impact of parental incarceration on the child(ren) and family from the perspective of the incarcerated parent.MethodsA convenience sample of 26 parents incarcerated in an urban county jail were interviewed. Parents were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Ultimately, children may fear for their incarcerated parent's safety. Correa et al (2021) suggested that young children generally have difficulty in understanding and grasping the nature of carceral systems. In the absence of clear communication about their parents, children's imaginations may leave them with unrealistic and growing anxieties.…”
Section: Parental Incarcerationmentioning
confidence: 99%
“…Ultimately, children may fear for their incarcerated parent's safety. Correa et al (2021) suggested that young children generally have difficulty in understanding and grasping the nature of carceral systems. In the absence of clear communication about their parents, children's imaginations may leave them with unrealistic and growing anxieties.…”
Section: Parental Incarcerationmentioning
confidence: 99%
“…Since then, the effects of ACEs have been studied in individuals at various phases of the human life span ( Brown et al, 2010 ; Isohookana et al, 2013 ; Crandall et al, 2020 ; Elmore et al, 2020 ). Parental incarceration, for example, has been reported to create significant challenges for children and families, such as maintaining parent-child relationships, throughout childhood and adolescence ( Correa et al, 2021 ). As well, the co-occurrence of multiple ACEs is a risk factor for a myriad of health conditions, including diabetes, chronic lung disease, depression, and suicidality, as well as risky behaviors like early sexual initiation and violence perpetration (see Hughes et al, 2017 for review).…”
Section: Introductionmentioning
confidence: 99%
“…Children who do not acquire this attachment are at a higher risk for antisocial behavior (Marcus & Betzer, 1996) and delinquency (Hoeve et al, 2012). Recent literature has also illustrated incarcerated families' difficulties that impact their relationships with their children and spouses (Correa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Children who do not acquire this attachment are at a higher risk for antisocial behavior (Marcus & Betzer, 1996) and delinquency (Hoeve et al, 2012). Recent literature has also illustrated incarcerated families' difficulties that impact their relationships with their children and spouses (Correa et al, 2021). The current investigation examines the potential impacts of incarceration on parent-child relationships as they relate to visitation and maintaining these relationships.…”
Section: Introductionmentioning
confidence: 99%